2017
DOI: 10.1186/s41065-017-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure analysis of Kala bhat (Glycine max (L.) Merrill) genotypes using SSR markers

Abstract: BackgroundKala bhat (Black soybean) is an important legume crop in Uttarakhand state, India, due to its nutritional and medicinal properties. In the current study, the genetic variabilities present in Kala bhat were estimated using SSR markers and its variability was compared with other improved soybean varieties cultivated in Uttarakhand state, India.ResultsSeventy-five genotypes cultivated in different districts of Uttarakhand were collected, and molecular analysis was done using 21 SSR markers. A total of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
5
17
1
Order By: Relevance
“…Genotype GMSE0634 (0.5) had the lowest heterozygosity value, whereas Satt001 (0.87) had the highest value. The average heterozygosity value obtained was 0.7485 and were much higher than results reported values on soybean (Wang et al, 2006;Li et al, 2008;Wang et al, 2010;Zhang et al, 2013;Hipparagi et al, 2017) . Figure 1 shows a dendrogram for the 30 soybean genotypes constructed using the unweighted pair group method with arithmetic mean (UPGMA) clustering algorithm based on 20 SSR markers.…”
Section: Introductioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Genotype GMSE0634 (0.5) had the lowest heterozygosity value, whereas Satt001 (0.87) had the highest value. The average heterozygosity value obtained was 0.7485 and were much higher than results reported values on soybean (Wang et al, 2006;Li et al, 2008;Wang et al, 2010;Zhang et al, 2013;Hipparagi et al, 2017) . Figure 1 shows a dendrogram for the 30 soybean genotypes constructed using the unweighted pair group method with arithmetic mean (UPGMA) clustering algorithm based on 20 SSR markers.…”
Section: Introductioncontrasting
confidence: 62%
“…Recently, Bisen et al (2015) reported two major clusters, which were further divided into two sub-groups in the analysis of 38 soybean genotypes using 16 SSR markers. In addition, Hipparagi et al (2017) found three distinct clusters in 75 genotypes using 21 SSR markers, and Hirota et al Wang et al (2006) and Ghosh et al (2014) observed two major clusters. A previous study on revolutionary relationship between Glycine soja and Glycine max revealed two clusters (Wen et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study detected a total of 71 alleles with an average of 2.8 alleles per locus. Seventyfive soybean genotypes of soybean were analyzed for genetic variability using 21 SSR markers (Hipparagi et al, 2017). A total of 60 alleles were amplified with an average of 2.85 alleles per locus.…”
mentioning
confidence: 99%